BURUNG BANGAU DALAM KARYA LUKISAN BATIK - Geza Maira Putri; Erwin Erwin (Universitas Negeri Padang, 2021)
The bluwok heron is a water bird that has a rather large body than other storks, has long legs and neck and moves wherever he wants. But now the Bluwok crane is threatened with extinction. Such a situation encourages the writer to make it an idea to create hand-written batik in the form of paintings. Through five stages of embodiment, that is: preparation, elaboration, synthesis, concept realization, and completion stage which were successfully realized by: 1) Menyelisik, 2) Mengaso, 3) Memadu Kasih, 4) Datang, 5) Lepas Landas, 6) Uji Coba, 7) Berbagi, 8)Persiapan , 9) Setujuan, 10) Tertinggal.. This work is recommended so that ideas and techniques can be developed in the future.Key words: Heron, Batik Painting